Drimane Derivatives as the First Examples of Covalent BH3 Mimetics that Target MCL‐1. (23rd March 2021) - Daressy, Florian; Malard, Florian; Seguy, Line; Guérineau, Vincent; Apel, Cécile; Dumontet, Vincent; Robert, Aude; Groo, Anne‐Claire; Litaudon, Marc; Bignon, Jérôme; Desrat, Sandy; Malzert‐Fréon, Aurélie; et al.
Abstract: Drimane sesquiterpenoid dialdehydes are natural compounds with antiproliferative properties. Nevertheless, their mode of action has not yet been discovered. Herein, we demonstrate that various drimanes are potent inhibitors of MCL‐1 and BCL‐xL, two proteins of the BCL‐2 family that are overexpressed in various cancers, including lymphoid malignancies. Subtle changes in their structure significantly modified their activity on the target proteins. The two most active compounds are MCL‐1 selective and bind in the BH3 binding groove of the protein. Complementary studies by NMR spectroscopy and mass spectrometry analyses, but also synthesis, showed that they covalently inhibit MCL‐1 though the formation of a pyrrole adduct. In addition, cytotoxic assays revealed that these two compounds show a cytotoxic selectivity for BL2, a MCL‐1/BCL‐xL‐dependent cell line and induce apoptosis. Abstract : Covalent inhibitors inducing apoptosis : Specific natural drimane derivatives are covalent BH3 mimetics that target MCL‐1, an anti‐apoptotic protein of the BCL‐2 family. They react via a Paal‐Knorr rearrangement with a lysine of the protein to yield pyrrole adducts.